The Two Faces of SLA: Mental Representation and Skill - Bill Van Patten (International Journal of English Studies (IJES), 2010)
In this essay, I argue for viewing mental representation and skill as distinct components of language acquisition. My claim is that language is not a monolithic entity—not a new concept, but one that is often overlooked by instructors and some scholars. I examine language as being (minimally) composed of mental representation and skill. Representation refers to the abstract and implicit knowledge that underlies all language. Skill refers to the use of language, especially fluency (the intersection of speed and accuracy). By thinking about language as at least the distinction between representation and skill, we might better sort out some of the issues related to adult SLA, namely the role that instruction has, and what instruction can actually impact. En este trabajo defiendo el supuesto de que tanto la representación mental como las destrezas (lingüísticas) deben ser tomadas como componentes diferenciados de la adquisición lingüística. Mi tesis es que el lenguaje no es una entidad monolítica –tesis no nueva, pero frecuentemente dejada de lado por profesores y estudiosos. Analizo el lenguaje como un compuesto de representación mental y destrezas. La representación se refiere al conocimiento abstracto e implícito que subyace en el lenguaje. Las destrezas hacen referencia al uso de la lengua, especialmente a la fluidez (intersección entre velocidad y precisión). Entendiendo el lenguaje de esta manera, distinguiendo entre representación y destrezas, será posible superar algunos de los problemas relativos al aprendizaje de lenguas por los adultos, y muy especialmente el cometido de la enseñanza y lo que ésta puede producir.